Effect of Vitamin E Therapy on Children With Renal Stones - Taherahmadi, Hasan; Arjmand Shabestari, Ali; Yousefichaijan, Parsa; Mohaghegh, Pegah; Bahadoran, Salehe; Toghra, Alireza (Journal of Pediatric Nephrology, 2025)
Background and Aim: Urinary system stones, including kidney stones, are common diseases of the kidney and urinary tract that have increased over time. The treatment of these patients, especially in children, is of great importance. This study evaluated the effect of vitamin E on the treatment of children with kidney stones. Methods: This double-blind, randomized controlled trial (RCT) was conducted on children between the ages of 2 and 18 years with a diagnosis of kidney stones. The samples were randomly divided into two groups: The intervention group, which received vitamin E in addition to standard treatment, and the control group, which received standard treatment. This division was blinded to the evaluator and the patients. Information about the condition of the stones before and after treatment was obtained from two sources and compared using SPSS statistical software. Results: The mean age (P=0.595) and frequency distribution of gender (P=0.685) showed no statistically significant difference between the two groups. The mean number of stones before treatment in the intervention group was 3.04±1.87, while in the control group, they were 3.22±2.01, indicating no significant difference according to the independent t-test. After treatment, values were 1.15±1.3 in the intervention group and 2.34±1.75 in the control group. The mean size of the largest stone in the intervention group before treatment was 0.09±0.34 cm, and after treatment, it was 0.18±0.07 cm (P=0.964). In the control group, the size of the largest stone before treatment was 0.10±0.32 cm, and after treatment, it increased to 0.25±0.1 cm, which was significantly smaller in the intervention group based on the independent t-test. Conclusion: The use of vitamin E can reduce the size and number of kidney stones in children.